DEVELOPMENT AND EVALUATION OF NANOEMULSION AS A CARRIER FOR TOPICAL DELIVERY SYSTEM BY BOX-BEHNKEN DESIGN - Chaudhari, Pallavi M; Kuchekar, Madhavi A (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to develop a nanoemulsion for topical delivery. Methods: Topical nanoemulsion was prepared by homogenization method. Box-behnken design was utilized to study the effect of oil, surfactant and Co-surfactant, on droplet size, entrapment efficiency and drug release. Nabumetone a non-steroidal anti-inflammatory drug was incorporated in castor oil with Tween 80 and Polyethylene glycol 600 to form the nanoemulsion by homogenization method. The nanoemulsion was further subjected to different evaluation parameters and ex-vivo study. The crystalline nature of drug was confirmed by powder X-ray diffraction studies. Drug-excipient compatibility was confirmed by Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), respectively. Results: The average globule size of nabumetone-containing nanoemulsion decreased with decrease in concentration of oil and surfactant. Nanoemulsion was evaluated by pH, rheology, globule size, zeta potential, scanning electron microscopy, DSC, FTIR spectroscopy, and stability. In vitro drug release shows maximum 84.35% permeation rate through cellophane membrane and ex-vivo drug release shows 86.32% permeation rate through goat skin. Conclusion: Thus, the nanoemulsion formulated showed good results regarding topical delivery.